Using nonlinear models to describe height growth curves in Pantaneiro horses - Santos, Sandra Aparecida; Souza, Geraldo da Silva e; Oliveira, Marcos Ruben de; Sereno, José Robson (Pesquisa Agropecuaria Brasileira, 1999)
Height at withers data mostly from birth to 36 months of age of 26 Pantaneiro horses were used to fit Brody, Richards, Gompertz, Logistic, Weibull and Morgan-Mercer-Flodin nonlinear response functions. Based on measures of average curvature and combined mean square error, the Weibull model was chosen. The asymptote of this curve, representing the average height at maturity, was higher for males than females. The maturity index, however, was more elevated for females than males. There was indication of a negative association between the maturity index and height at maturity only for females. These results indicate that females mature earlier. After checking for normality and homogeneity of variances within groups (sex) the analysis investigated sex differences via t-tests. A significant difference was detected only for height at birth.